Diclofenac but not celecoxib improves endothelial function in rheumatoid arthritis: A study in adjuvant-induced arthritis. (November 2017) - Verhoeven, Frank; Totoson, Perle; Marie, Christine; Prigent-Tessier, Anne; Wendling, Daniel; Tournier-Nappey, Maude; Prati, Clément; Demougeot, Céline
Abstract: Background and aims: We aimed at investigating the effect of celecoxib (COX-2 selective inhibitor) and diclofenac (non-selective COX inhibitor) on endothelial function, and at identifying the underlying mechanisms in adjuvant-induced arthritis (AIA). Methods: At the first signs of AIA, diclofenac (5 mg/kg twice a day, i.p), celecoxib (3 mg/kg/day, i.p) or saline (Vehicle) was administered for 3 weeks. Endothelial function was studied in aortic rings relaxed with acetylcholine (Ach) with or without inhibitors of NOS, arginase, EDHF and superoxide anions (O2 −° ) production. Aortic expression of eNOS, Ser1177-phospho-eNOS, COX-2, arginase-2, p22 phox and p47 phox was evaluated by Western blotting analysis. Arthritis scores, blood pressure, glycaemia and serum ADMA levels were measured. Results: Diclofenac and celecoxib significantly reduced arthritis score to the same extent ( p <0.05). As compared to vehicle-treated AIA, celecoxib did not change whereas diclofenac improved endothelial function ( p <0.05) through increased EDHF production, decreased arginase activity and expression, decreased superoxide anions production and expression of p22 phox and p47 phox . Diclofenac but not celecoxib significantly enhanced blood pressure and serum ADMA levels. Glycaemia was unchanged by both treatments. Conclusions: Our study reveals that the effect of NSAIDs on endothelial function cannot be extrapolated from their impact on arthritis severity and suggest that changes in blood pressure and plasma ADMA levels may not be useful to predict CV risk of NSAIDs in RA. Graphical abstract: Highlights: Diclofenac improved endothelial function in adjuvant induced arthritis. Diclofenac reduced O2 −° production, arginase activity/expression, enhanced EDHF production but not NOS activity/expression. Celecoxib did not improve endothelial function even if it was beneficial on arthritis.